2019
DOI: 10.4149/neo_2019_190106n21
|View full text |Cite
|
Sign up to set email alerts
|

TRIM31 promotes proliferation, invasion and migration of glioma cells through Akt signaling pathway

Abstract: This study is intended to investigate the role of Tripartite Motif (TRIM) 31 in glioma. Immunohistochemistry and western blot analysis showed that TRIM31 was overexpressed in high-grade glioma tissues. Univariate survival analysis indicated that high expression of TRIM31 was related to short survival time of glioma patients. Multivariate survival analysis demonstrated that TRIM31 was an independent prognostic factor for glioma patients. In addition, through the experiments on glioma cell lines, we found that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…TRIM31 occupies center stage in human hepatocellular carcinoma by upregulating the mTORC1 signaling pathway (Guo et al, 2018). TRIM31 promotes proliferation, invasion, and migration of glioma cells via protein kinase B signaling pathway or by activating the nuclear factor κB (NF‐κB) pathway (Shi et al, 2019; Zhou et al, 2019). TRIM31 promotes invasion and metastasis in colorectal cancer by regulating chronic inflammation through the NF‐κB signaling pathway (H. Wang, Yao, Gong, & Zhang, 2018), but it is also a tumor suppressor, inhibiting malignant cancer growth of non‐small‐cell lung cancer (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TRIM31 occupies center stage in human hepatocellular carcinoma by upregulating the mTORC1 signaling pathway (Guo et al, 2018). TRIM31 promotes proliferation, invasion, and migration of glioma cells via protein kinase B signaling pathway or by activating the nuclear factor κB (NF‐κB) pathway (Shi et al, 2019; Zhou et al, 2019). TRIM31 promotes invasion and metastasis in colorectal cancer by regulating chronic inflammation through the NF‐κB signaling pathway (H. Wang, Yao, Gong, & Zhang, 2018), but it is also a tumor suppressor, inhibiting malignant cancer growth of non‐small‐cell lung cancer (Li et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This study identified differential DNA methylation associated with the herbicide glyphosate and its metabolite AMPA and developed a methylation index that accurately predicted urinary glyphosate concentration and tertile in an internal validation sample. Glyphosate- and AMPA-associated methylation occurred near genes associated with cancer ( SF3B2, 109 , 110 , 111 MSH4, 113 and TRIM31 117 , 118 , 119 ) and endocrine disruption ( ESR1 132 ), and AMPA was associated with greater epigenetic age acceleration. These results suggest that exposure to these common chemicals affects the epigenome, informing the hypothesis that glyphosate and/or AMPA exposure might elevate the risk for disease, including cancer.…”
Section: Discussionmentioning
confidence: 96%
“… 113 ERCC8 is also involved in DNA repair via transcription-coupled nucleotide excision repair and double-strand break repair. 114 , 115 , 116 Hypomethylation at TRIM31 , which has been shown to promote progression in a variety of tumor types, 117 , 118 , 119 was associated with AMPA. The AMPA-associated hypomethylation at the ESR1 promoter is fascinating, given the potential link between AMPA and breast cancer risk 23 , 32 and the potential for glyphosate-induced endocrine disruption.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased TRIM31 expression was associated with elevated p-Akt (S473), PCNA and E-cadherin expression. By using Akt agonists in TRIM31 -silenced cells or Akt antagonists in TRIM31-overexpressing cells, it was shown that TRIM31 mediates tumorigenesis through Akt signaling [ 95 ] ( Figure 2 a).…”
Section: Trim Proteins In Brain Tumorsmentioning
confidence: 99%